ENGLISH USE IN FACEBOOK USERS’ STATUS - Kasmi, Hasni Il; Junaid, Syahruni (Study Program of English Literature, 2018)
This research discussed about English Use in Facebook Users’ Status which aimed to analyze the kinds of language style in Facebook Users’ Status and the dominant of it. The source of the data based on the Facebook User’s status who wrote theirs in English. This research based on Mandell and Krisner theory about language style. This research was descriptive qualitative method. The research used note taking as the instrument in order to get valid data. the findings showed that there were four styles that used by Facebook Users in writing their status those were 9 data of formal, 13 data of informal 7 data of slang, 10 data colloquial. The researcher concluded that the dominant of language that the Facebook users used is 13 data of informal style based on the quantity and they almost used language style in updating their status on Facebook.